PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMP MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION DAN BUZZ GROUP (Studi Komparatif pada Kelas VII SMPN 3 Parongpong, Bandung Barat) - Hutapea, Ellen Nadya; Tauran, Sonya Fanny (Jurnal Padegogik, 2018)
This study aims to improve the mathematical communication ability of junior highschool students. Research using cooperative learning model type Student Teams AchievementDivision (STAD) and Buzz Group type. This research uses two classes namely class VII-A andVII-E SMPN 3 Parongpong, West Bandung. The test instrument is a test of mathematicalcommunication ability on the subject of data presentation. Non-test instruments are aquestionnaire of student responses to know their preferences and benefits for mathematicslearning. The test used is t-test at the 0.05 significance level. The results showed that: 1)Student's mathematical communication ability before obtaining cooperative learning typeStudent Teams Achievement Division (STAD) and Buzz Group type are not different and are inlow category. After the treatment of mathematical communication experience Improvement.Increased mathematical communication ability of students who obtained cooperative learningmodel type Student Teams Achievement Division (STAD) and Buzz Group type increased inhigh category, 2) There was no significant difference in the improvement of mathematicalcommunication ability between students who obtained cooperative learning model type StudentTeams Achievement Division (STAD) and Buzz Group type, 3) Student response indicates thatstudents are very fond of cooperative learning model of Student Teams Achievement Division(STAD) type and Buzz Group type.